Examining the value relevance of financial statements in European countries: the importance of legal origins on cross listing decisions - Alexios Kythreotis; Kyriakos Christofi; Milad Soltani (Cogent Business & Management, 2024)
In today's globalized competitive landscape several dimensions such as labour, markets and capital are integrated. As a result, companies attempt to gain inbound foreign capital. To achieve that they investigate away countries to host their operations and to trade their shares. While the concept of cross-listing strategy provides several benefits to companies, it has also critical challenges that companies are called to tackle. Different legal systems set different boundaries to investors power. With the application of criterion sampling, we utilize a multiple regression analysis in the European stock exchanges, for a period of eight years, and we investigated the impact of legal origins on financial statements' value relevance. The findings indicate that common law countries offer a more beneficial environment for cross-listing strategies, as they demonstrate greater value relevance in financial statements compared to civil law countries. Specifically, our results show that both Profit or Loss and Balance Sheet items are more relevant in common law countries compared to civil law countries.
Keywords: 650; Value relevance; legal origins; common law; civil law; cross listing; IFRS